CRISPR, Recombinant DNA, and LAMP-Based Platforms for Monkeypox: Emerging Tools for Diagnosis and Therapeutic Development - Yukti Sabikhi; Anshika Singh; Sameen Masroor; Chhavi Dudeja; Sanya Kaushik; Khushi Tyagi (International Journal of Virus Studies, 2026)
Monkeypox, a zoonotic viral infection caused by the Monkeypox virus of the Orthopoxvirus genus, has recurred as a worldwide public health concern after recent outbreaks outside of its classical endemic areas in Central and West Africa. The resurgence has demanded a thorough reassessment of its epidemiology, mode of transmission, and clinical presentation. In light of these challenges, recombinant DNA technology (rDNA) has emerged as a candidate for developing vaccines, diagnostics, and therapeutic agents, as shown in the successful control of other viral diseases like hepatitis B and HPV. The combination of rDNA and CRISPR-based methods presents a revolutionary strategy for monkeypox surveillance and control. CRISPR-Cas systems—particularly Cas12a and Cas13a—have been shown to be effective for sensing MPXV with high sensitivity and specificity through fluorescence, lateral flow, and smartphone-based readouts. Challenges still exist in crRNA design, assay optimization, and standardization. Furthermore, Loop-mediated Isothermal Amplification (LAMP) directed against A27L and F3L genes of MPXV has shown encouraging sensitivity and specificity and was superior to traditional PCR approaches in some contexts. These diagnostic gains are matched by continued clinical trials for both conventional and emerging vaccine platforms—including MVA-BN, JYNNEOS, and RNA-based constructs such as BNT166a—and antiviral drugs like Tecovirimat. All the same, rapid diagnosis and availability of therapeutics remain significant challenges to monkeypox management. This review brings out the important contribution of new biotechnological tools, specifically rDNA, CRISPR, and LAMP, in revolutionizing existing diagnostic and treatment methods, hence leading to efficient disease management and future outbreak readiness.
Keywords: CRISPR; Loop-mediated Isothermal Amplification (LAMP); Monkeypox virus; Recombinant DNA technology; Tecovirimat; assay optimization